Argumentation Theory: A Pragma-Dialectical Perspective - van Eemeren, Frans H. (Argumentation Library,, 2018)
The book offers a compact but comprehensive introductory overview of the crucial components of argumentation theory. In presenting this overview, argumentation is consistently approached from a pragma-dialectical perspective by viewing it pragmatically as a goal-directed communicative activity and dialectically as part of a regulated critical exchange aimed at resolving a difference of opinion. As a result, the book also systematically explains how the constitutive parts of the pragma-dialectical theory of argumentation, which are discussed in a number of separate publications, hang together. The following crucial topics are discussed: (1) argumentation theory as a discipline; (2) the meta-theoretical principles of pragma-dialectics; (3) the model of a critical discussion aimed at resolving a difference of opinion; (4) fallacies as violations of a code of conduct for reasonable argumentative discourse; (5) descriptive research of argumentative reality; (6) analysis as theoretically-motivated reconstruction; (7) strategic manoeuvring aimed at combining achieving effectiveness with maintaining reasonableness; (8) the conventionalization of argumentative practices; (9) prototypical argumentative patterns; (10) pragma-dialectics amidst other approaches. Argumentation Theory: A Pragma-Dialectical Perspective is clearly written and makes argumentation theory understandable to all scholars and advanced students interested in argumentation research.